2017
DOI: 10.1021/acs.jpca.7b09185
|View full text |Cite
|
Sign up to set email alerts
|

Conserving Coherence and Storing Energy during Internal Conversion: Photoinduced Dynamics of cis- and trans-Azobenzene Radical Cations

Abstract: Light harvesting via energy storage in azobenzene has been a key topic for decades and the process of energy distribution over the molecular degrees of freedom following photoexcitation remains to be understood. Dynamics of a photoexcited system can exhibit high degrees of nonergodicity when it is driven by just a few degrees of freedom. Typically, an internal conversion leads to the loss of such localization of dynamics as the intramolecular energy becomes statistically redistributed over all molecular degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 46 publications
(115 reference statements)
4
39
0
Order By: Relevance
“…The large yield of parent 2-NT + as compared to previously reported mass spectra taken with femtosecond lasers 5,17,18 is consistent with the expected adiabatic ionization process at 1300 nm excitation. 22,35,36,[38][39][40][41] with the oscillations of the smaller fragment ions, consistent with coherent excitation by the probe pulse. 22,[29][30][31][32][33][34][35][36][37][38][39] The same transient dynamics with smaller-amplitude features were observed for lower pump and probe intensities (Supporting Information, Figure S4).…”
Section: Theorymentioning
confidence: 70%
See 2 more Smart Citations
“…The large yield of parent 2-NT + as compared to previously reported mass spectra taken with femtosecond lasers 5,17,18 is consistent with the expected adiabatic ionization process at 1300 nm excitation. 22,35,36,[38][39][40][41] with the oscillations of the smaller fragment ions, consistent with coherent excitation by the probe pulse. 22,[29][30][31][32][33][34][35][36][37][38][39] The same transient dynamics with smaller-amplitude features were observed for lower pump and probe intensities (Supporting Information, Figure S4).…”
Section: Theorymentioning
confidence: 70%
“…shown in Figure 13 hexadiene, 65 benzonitriles, 66,67 Rydberg states of N -methyl morpholine, 60,61 and azobenzene radical cation. 38 CO loss from excited-state metal hexacarbonyls has also been reported to result in coherent vibrational motion of the remaining metal pentacarbonyl. [68][69][70] We attribute this unexpected behavior to the exceptionally fast H-atom attack within ∼ 20 − 60 fs, which maintains the localized vibrational excitation along the torsional coordinate.…”
Section: Int1r Int2mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the presence of multiple coupled normalm odes leads to fast dephasing of initially prepared vibrational wave packets in polyatomic radical cations within atm ost several picoseconds of the initial ionization event. Nevertheless, coherenti on yield oscillations have been observed in many classes of polyatomic radical cations including halomethanes, [32,33] 1,3-dibromopropane, [34] azobenzene, [35] alkyl aryl ketones, [21,36,37] nitrotoluenes, [27,38] and methylphosphonates. [22,39] Although in most cases, the ion yield oscillations are attributed to dynamics on D 0 ,d ynamics on excited ionic states have also been reported.…”
Section: Illustrationsmentioning
confidence: 99%
“…Theg round-state geometries of several species participating in the photoregulating process,including cis-/trans-Azo, cis-/trans-Azo + ,and diisobutyronitrile radical/ anion (RC/R À ), were optimized using the DFT/B3LYP/PCM method (Supporting Information, Figure S13). [21] Thegroundstate energies of the above species were calculated and the molecular orbitals showed the preferential geometry and the charge localization ( Figure 3). Theexcitation energies of cisor trans-Azo for the S 1 (n-p*) state were calculated using the EOM-CCSD method, and it is found that the energy levels of the HOMO orbitals of cis-a nd trans-Azo are lower than the LUMO orbitals of diisobutyronitrile radical (Figure 3), and almost no electronic transition absorption occurs in trans-Azo (2.95 eV with an oscillator strength of f = 0.0000).…”
Section: Angewandte Chemiementioning
confidence: 99%